The proportion of different interleukin‐17‐producing T‐cell subsets is associated with liver fibrosis in chronic hepatitis C. Issue 2 (13th March 2017) - Cachem, Fabio C. O. F.; Dias, Aleida S.; Monteiro, Clarice; Castro, José Roberto; Fernandes, Gabriel; Delphim, Letícia; Almeida, Adilson J.; Tavares, Felipe; Maciel, Alessandra M. A.; Amendola‐Pires, Marcia M.; Brandão‐Mello, Carlos E.; Bento, Cleonice A. M.
Summary: Studies have suggested the pivotal role of T helper type 1 (Th1) ‐related cytokines on the outcome of hepatitis C virus (HCV) infection. Nevertheless, the role of different interleukin‐17 (IL‐17) ‐secreting T cells on chronic hepatitis C (CHC) is less clear. Here, the in vivo IL‐1 β, IL‐6, and IL‐17 levels were positively correlated with both alanine transaminase (ALT) levels and hepatic lesions. When compared with the control group, CHC patients showed a lower proportion of IL‐17‐secreting (CD4 + and CD8 + ) T cells capable of simultaneously producing IL‐21. Moreover, the percentage of IL‐10‐secreting Th17 cells was also lower in CHC patients. Notably, advanced liver lesions were observed among those patients with lower percentage levels of IL‐17‐producing T cells positive for IL‐21, interferon‐ γ (IFN‐ γ ) and IL‐10. In contrast, the severity of hepatic damage was associated with peripheral single IL‐17 + T cells. The percentage of IL‐17 + IL‐21 – IFN‐ γ + (CD4 + and CD8 + ) T‐cell phenotypes was positively associated with plasma CD14 levels. Finally, elevated levels of circulating CD14 were detected among CHC patients with extensive liver damage. In summary, although preliminary, our results suggest that a balance between different IL‐17‐producing T cells, associated with peripheral levels of CD14, may be a progress marker for liver disease in chronically HCV‐infected patients. Abstract : In patients with chronic hepatitis C, liver lesion was directly associated with percentage of peripheral IL‐17 + IL‐21 – IFN‐ γ – T cells. The production of IL‐21 or IFN‐ γ by Th17 or Tc‐17 cells was positively associated with lower liver fibrosis in chronically HCV‐infected patients Elevated levels of circulating CD14 were detected in HCV‐infected patients with high liver damage.